"Managerial 'styles' in Industrial Relations: Forecasting trends in the next decade" - Johari, Husna (Perbadanan Produktiviti Negara, 1993)
The are a o f managerial 'styles' has proved to be both controversial and useful for discussion in the context of industrial relations.It is useful particularly to contrast in order to understand the main managerial 'styles' in industrial relation because the managers are important and a rapidly expanding integral group in all industrial relations system sand societies.In this discussion,a comparative and cross-national reference is taken in contrasting the managerial 'style' being practised amongst nations. Thus the elements of cultural values and ideologies are basic to the under standing of managerial 'styles' in industrial relations in a particular country.At the enterprise or organization level there exist a close inter link between the managerial strategy and style practised. It is also vital to be aware of the constraints which have impact son a particular managerial style choose n which include the economic forces, politico-economic systems,socio-cultural structures, organization structures, the role and relationship of trade unions, employers associations,the role of government and the statutory requirements of a particular country with regard to contraints there a rise various differentiable 'hybrid' styles being practised today.